Stop and restart of granular clock in a vibrated compartmentalized bidisperse granular system - Liu, Q.; Hu, M.; Jiang, R.; Wu, Yong Hong (The American Physical Society, 2013)
This paper studies a bidisperse granular mixture consisting of two species of stainless steel spheres in a vertically vibrated compartmentalized container. The experiments show that with proper vibration acceleration, the granular clock stops when horizontal segregation of the large spheres residing in the far end from the barrier wall occurs. When the segregation is broken, the granular clock restarts. We present the phase diagrams of vibration acceleration versus container width and small particle number, which exhibits three different regions, namely, clustering state, stop-restart of the granular clock, and the granular clock. A generalized flux model is proposed to reproduce the phenomenon of stop and restart of the granular clock.